Factors that drive the gap in diabetes rates between Aboriginal and non‐Aboriginal people in non‐remote NSW - Rebecca Reeve; Jody Church; Marion Haas; Wylie Bradford; Rosalie Viney (Elsevier, 2014)
Abstract Objective: To identify factors underpinning the gap in diabetes rates between Aboriginal and non‐Aboriginal people in non‐remote NSW. This will indicate appropriate target areas for policy and for monitoring progress towards reducing the gap. Methods: Data from the 2004-05 National Health Survey and National Aboriginal and Torres Strait Islander Health Survey were used to estimate differences in self‐reported diabetes rates and risk/prevention factors between Aboriginal and non‐Aboriginal people in non‐remote NSW. Logistic regression models were used to investigate the contribution of each factor to predicting the probability of diabetes. Results: Risk factors for diabetes are more prevalent and diabetes rates 2.5 to 4 times higher in Aboriginal compared to non‐Aboriginal adults in non‐remote NSW. The odds of (known) diabetes for both groups are significantly higher for older people, those with low levels of education and those who are overweight or obese. In the Aboriginal sample, the odds of diabetes are significantly higher for people reporting forced removal of their relatives. Conclusions: Differences in BMI and education appear to be driving the diabetes gap, together with onset at younger ages in the Aboriginal population. Psychological distress, indicated by removal of relatives, may contribute to increased risk of diabetes in the Aboriginal population. Implications: The results imply that improved nutrition and exercise, capacity to access and act upon health care information and early intervention are required to reduce the diabetes gap. Current strategies appear to be appropriately aligned with the evidence; however, further research is required to determine whether implementation methods are effective.